Tolok Vladimir Tarasovich: to 80th anniversary of birthday - Neklyudov, I.M.; Azhazha, V.M.; Vishnevsky, I.N.; Zelensky, V.F.; Peletminsky, S.V.; Bakai, A.S.; Dovbnya, A.N.; Klepikov, V.F.; Slyezov, V.V.; Stepanov, K.N.; Shul’ga, N.F.; Tereshin, V.I.; et al. (Вопросы атомной науки и техники, 2007)
Vladimir Tarasovich Tolok, the Corresponding Member of Ukrainian Academy of Sciences, Doctor of Sciences, Professor, Honored worker of the Ukrainian Science, is the well-known scientist in the field of plasma physics and controlled fusion, who has made a lot for coming-to-be and development of this direction in Ukraine.